Implementasi Dialogic Reading Dalam Upaya Meningkatkan Attachment Antara Guru dan Siswa (Studi PenelitianTindakan Kelas di TK. An-Nuur Tanjungkamuning, Garut) - Pratiwi, Shelly; Al-Hasni, Sri Rezeki (LP2M STAI Al-Musaddadiyah Garut, 2022)
This research is motivated by the low level of attachment between teachers and students in Early Childhood Education institutions due to schedule changes and reduced teaching time during the Covid-19 pandemic. According to several studies, the dialogic reading method has an impact on various aspects of early childhood development. Therefore, the researcher is interested in further examining the application of this method to enhance the attachment between teachers and students at TK An-Nuur Tanjungkamuning. The aim of this study is to observe the improvement in attachment between teachers and students at TK An-Nuur before and after the implementation of the dialogic reading method. In this classroom action research, the population used is students in Group B at TK An-Nuur Tanjungkamuning, totaling 32 students, with a sample of 16 students from class B at TK An-Nuur Tanjungkamuning. This research uses a qualitative approach with data collection techniques. The research instruments used are observation and documentation techniques. Based on the analysis of the existing problems, this classroom action research is planned to consist of several stages: pre-cycle, cycle 1, and cycle 2. The attachment percentage in the pre-cycle was 0%. Then, in cycle 1, the success rate reached 87.5%. In cycle 2, there was an increase of 12.5%, resulting in a success rate of 100%. Keywords: Attachment, Dialogic Reading